Pertanggung Jawaban Notaris terhadap Pembuatan Akta Perjanjian Perikatan Jual Beli atas Objek Jaminan Kredit : Studi Putusan Nomor 4541 K/Pdt/2024 - Alfius Sitepu; tony; hasim purba (Jurnal Hukum Lex Generalis, 2026)
A notary, as a public official, is authorized to draft authentic deeds, including the Preliminary Sale and Purchase Agreement (PPJB). However, problems arise when the object stipulated in the agreement is still encumbered by a mortgage (hak tanggungan) as bank credit collateral, as reflected in Supreme Court Decision Number 4541 K/Pdt/2024. This normative juridical study examines the application of the principle of prudence by notaries, their responsibilities under the Notary Profession Law (UUJN) and the legal consequences of such negligence. The findings indicate that notaries are obligated to carefully examine the legal status of the object prior to drafting a PPJB. Negligence in this regard may give rise to administrative, civil and ethical liability; therefore, the application of the principle of prudence is crucial to ensuring legal certainty and protection for all parties, particularly consumers.